A systematic examination of the dynamics of water-cellulose interactions on capillary force-induced fiber collapse. (1st November 2022) - Salem, Khandoker Samaher; Naithani, Ved; Jameel, Hasan; Lucia, Lucian; Pal, Lokendra
Abstract: Cellulosic fiber collapse is a phenomenon of fundamental importance for many technologies that include tissue/hygiene to packaging because it governs their essential materials properties such as tensile strength, softness, and water absorption; therefore, we elaborate cellulose fiber collapse from water interactions. This is the first attempt to directly correlate fiber collapse and entrapped or hard-to-remove (HR) water content through DSC, TGA and SEM. Freeze-drying and oven drying were individually investigated for influence on collapse. SEM of the fibers at different moisture contents show that irreversible collapsing begins as entrapped water departs the fiber surface. The removal of HR water pulls cell walls closer due to strong capillary action which overwhelms the elastic force of the fiber lumen which results in partially or fully irreversible collapse. The initial moisture content and refining intensity were found to regulate HR water content and consequently played a vital role in fiber collapsing. Graphical abstract: Unlabelled Image